A complexidade no rádio: contribuições sobre o meio de comunicação na contemporaneidade sob a teoria de Edgar Morin - Freire, Danielson de Oliveira (2022)
Radio, understood as a communicational phenomenon of complexity, is the object of study in this master's research. The state of the art in research on radio in the communication field comprises works that investigate, in contemporary times, COVID-19 pandemic, digital convergence, mediatization, segmentations, genres and formats, types of radiophony, laws and regulations radiophonic etc., without researches on the complexity of radio. Thus, this research is justified by the originality of its approach. The research aims to conduct a semiotic study on radio and proposes interrelationships with the theory of complexity, as developed by Morin, and it will consist of four chapters, namely: (1) The phenomenon of radio, dedicated to analyzing radio in its contemporaneity and to present a study on the main constituent elements of radio; (2) Radio in the cyberspace era, which proposes relationships between radio and its manifestations in cyberspace; (3) Complexity as a criterion, which intends to present the main elements of this theory; (4) The complexities of radio. The main research question is: what are the complexities present in radio, understood as media, language and culture in the contemporary communicational context? The secondary research question is: which creation processes in radio reveal and/or enhance the communicational complexities in radio? To answer the questions, the present Masters will adopt the following methods: (1) research on the state of the art on radio; (2) review of the main elements of complexity theory; (3) proposal of relations between theory and radio in its historical, technological and communicational transformations; (4) Reflections on radio complexities and radio project cartographies in three case studies. The cartography method will be carried out according to Leão's conception. The research corpus consists of three radio programs, one per broadcaster, linked in their appropriate dials. It focused on observing – in the totality of each program – the radiophonic constituent elements as well as the hypermedia elements aggregated and interacting by the vehicle in its communicational modus. The cut was carried out through a ranking survey of the most accessed FM stations in São Paulo state, generated by the website radios.com.br. The stations and their chosen programs are: Bandeirantes radio with the program Os Donos da Bola; CBN São Paulo radio with the CBN São Paulo program and Antena 1 radio with the Antena 1 classics program. The theoretical framework is based on:complexity (Morin); radio, radio language, technology and man (Balsebre and Meditsch); cyberspace and the language of hypermedia (Leão and Santaella). Among the results, it is expected to develop a cartography of radio complexities that will contribute to the theoretical and practical study of this important communication phenomenon